Effective vemurafenib monotherapy for refractory Langerhans cell histiocytosis with sustained results post-withdrawal for over two years: a case report - Ren, Jiaxin; Gu, Ling; Tang, Xue (Frontiers in Oncology, 2025)
BackgroundLangerhans cell histiocytosis (LCH) is a rare, inflammatory myeloid neoplasm. Mitogen-activated protein kinase (MAPK) inhibitors, such as vemurafenib, can quickly control active disease in patients resistant to vinblastine and prednisone, but recurrence often occurs within a year after stopping treatment.Case presentationWe report the case of a 15-month-old girl with high-risk multisystem LCH and BRAFV600E mutation. The patient initially received treatment according to the LCH-III chemotherapy protocol but exhibited disease progression after two months of maintenance chemotherapy. Following initiation of vemurafenib monotherapy, the patient’s condition improved rapidly. The duration of vemurafenib monotherapy was one year and nine months. The patient remained disease-free for over two years after vemurafenib withdrawal.ConclusionThis case highlights the potential of MAPK inhibitor monotherapy for pediatric refractory LCH.